Glomerulonephritis in schistosomiasis mansoni: a time to reappraise - Rodrigues,Valério Ladeira (2010)
INTRODUCTION: The current prevalence of glomerulonephritis in patients with hepatosplenic schistosomiasis mansoni in Brazil was evaluated. METHODS: Sixty three patients (mean age 45.5±11 years) attending the outpatient infectious disease clinic of a University Hospital in Belo Horizonte, Brazil, from 2007 to 2009, were consecutively examined and enrolled in the present investigation. Diagnosis of hepatosplenic schistosomiasis was based on epidemiological, clinical and parasitological data and imaging techniques. Eight patients, who presented >30mg/day albuminuria, were submitted to percutaneous ultrasound guided renal biopsy. Kidney tissue fragments were examined under light, direct immunofluorescence and electron microscopy. RESULTS: All patients showed mesangial enlargement. In five, mesangial hypercellularity was observed and four presented duplication of the glomerular basement membrane. Areas of glomerular sclerosis were diagnosed in four. Deposits of immunoglobulin M and C3 were present in six samples; deposits of IgG in four, IgA in three and C1q in two samples. In all patients, immunoglobulin A was reported in the lumen of renal tubules. Deposits of kappa and lambda were observed in six samples. Electron microscopy revealed dense deposits in the glomerular tissue of three patients. Arterial hypertension, small esophageal varices, slight increases in serum creatinine and decreases in serum albumin were associated with glomerular disease. CONCLUSIONS: Renal disease associated with hepatosplenic schistosomiasis was verified in 12.7% of patients and type I membranoproliferative glomerulonephritis was observed in 50% of them. Schistosomal glomerulopathy still is an important problem in patients with hepatosplenic schistosomiasis in Brazil.